Preventive orthodontic approach for functional mandibular shift in early mixed dentition: A case report - Sharma, Divya S. (J Oral Biol Craniofac Res, 2019)
The case reported here highlights the importance of examination of functional occlusion along with static occlusion. Any undetected malocclusion during early mixed dentition has potency to alter the growth and function of stomatognathic system. Premature contacts in primary canine region is the most prevalent cause of functional mandibular shift and can lead to TMJ problems for the prevalence of self correction of such malocclusion is very low if not intervened. A case of functional mandibular shift due to faulty canine guidance because of premature contacts is discussed here. Selective grinding of premature contacts and myofunctional exercise resulted in well balanced centric occlusion coinciding with centric relation.